Using Macroeconomic Frameworks to Analyze the Impact of COVID-19 : An Application to Colombia and Cambodia - Bulir, Ales (Technical Notes and Manuals; Technical Notes and Manuals ;, 2021)
This technical note and manual (TNM) addresses the following issues: -- Evaluating the full implications from the policies adopted to mitigate the impact of the COVID-19 pandemic on the economy requires a well-developed macroeconomic framework. This note illustrates how such frameworks were used to analyze Colombia and Cambodia's shock impact at the beginning of the pandemic. -- The use of macroeconomic frameworks is not to infer general policy conclusions from abstract models or empirical analysis but to help policymakers think through and articulate coherent forecasts, scenarios, and policy responses. -- The two country cases illustrate how to construct a baseline scenario consistent with a COVID-19 shock within structural macroeconomic models. The scenario is built gradually to incorporate the available information, the pandemic's full effects, and the policy responses. -- The results demonstrate the value of combining close attention to the data, near-term forecasting, and model-based analyses to support coherent policies.